The replication initiator protein pi of the plasmid R6K specifically interacts with the host-encoded helicase DnaB. - Ratnakar, P V (1996)
The replication initiator protein pi of plasmid R6K is known to interact with the seven iterons of the gamma origin/enhancer and activate distant replication origins alpha and beta (ori alpha and ori beta) by pi-mediated DNA looping. Here we show that pi protein specifically interacts in vitro with the host-encoded helicase DnaB. The site of interaction of pi on DnaB has been localized to a 37-aa-long region located between amino acids 151 and 189 of DnaB. The surface of pi that interacts with DnaB has been mapped to the N-terminal region of the initiator protein between residues 1 and 116. The results suggest that during initiation of replication, the replicative helicase DnaB is first recruited to the gamma enhancer by the pi protein. In a subsequent step, the helicase probably gets delivered from ori gamma to ori alpha and ori beta by pi-mediated DNA looping.